(f○g)(x)=f(g(x))
(f○g)(x)=6(4x+1)
(f○g)(x)=24x+6
Answer:
radius ≈ 10.77 cm
Step-by-step explanation:
The segment from the centre O to the chord is a perpendicular bisector.
Thus 2 right triangles are formed with legs 10 cm and 4 cm ( half of XY )
The radius r is the hypotenuse.
Using Pythagoras' identity, then
r² = 4² + 10² = 16 + 100 = 116 ( take the square root of both sides )
r =
≈ 10.77 cm ( to 2 dec. places )
1. Correct answer is a (since when you are not given the n values, it is implied that the first value is 1).
3. Correct answer is a (a(n)=-3+4(1-1)=-3).
7. The pattern is to reduce the previous value by 4, thus the 12th term of the sequence is -24 (a(n)=20 - 4(n-1)=20 - 4(12-1)=-24).
8. Missing term is 26 (32+20=52; 52/2=26).
10. Pattern is 625/1=625; 625/5=125; 125/5=25; 25/5=5, thus. the 10th term is 1/3125 (answer a).
Answer:
A
Step-by-step explanation:
Hello There!
The y value of ABC was subtracted by 7 to get to the figure A'B'C'
So the rule for the given transformation would be
(x,y) ---> (x,y-7)
Firstly, for it to be a trinomial the expression would have to be x^2+5x+6 to factor this we would simply have to find 2 numbers that add up to 5 and multiply to 6. 3+2=5 and 3•2=6 so (x+3)(x+2) would be the answer